The Role of Collaboration and Coordination In Social Work Practice - Nedreta Šerić (Društvene i Humanističke Studije, 2021)
Social work, in the theoretical discourse, is an interdisciplinary and multidisciplinary occupation. This fact has been confirmed throughout the history of the development of social work and has inevitably been reflected in practice. Social workers need to collaborate and coordinate, in everyday practice, with different services, agencies, institutions, and organizations. There is a legal framework for a multi-sector approach, namely for the participation of stakeholders from the governmental, non-governmental, civil, and private sectors, but also from the ranks of religious communities and individuals. The focus of this paper is to analyze the role of collaboration and coordination through the scope of theory and practice, in different areas of professional practice of social work. Collaboration is important on many different levels, as well as coordination of agendas designed by different stakeholders. Perceived as connective elements, collaboration and coordination make way for more efficient social activities, optimal use of resources, and timely social reaction to different issues and social needs of a specific local community. In a wider context, this also leads to raising the level of efficiency, which is a significant issue in contemporary social work practice. Furthermore, this paper will also shed a light on possibilities and limitations, causes, and reasons for collaboration, as well as on different kinds of collaboration and problems in the process of establishing and maintaining the collaboration. The paper also includes legal background and research focused on collaboration and coordination in social work.